Combining Effect and Process Evaluation on European Preschool Children’s Snacking Behavior in a Kindergarten-Based, Family-Involved Cluster Randomized Controlled Trial: The ToyBox Study - De Craemer, Marieke (Int J Environ Res Public Health, 2020)
This study aimed at (1) studying the effect of the standardized ToyBox intervention on European preschoolers’ snacking behavior, and (2) studying whether a higher process evaluation score from teachers and parents/caregivers was associated with a more positive result for preschoolers’ snack intake. A sample of 4970 preschoolers (51.4% boys, 4.74 ± 0.44 years) from six European countries provided information on snack intake with the use of a Food Frequency Questionnaire. To investigate the effect of the intervention, multilevel repeated measures analyses were executed for the total sample and the six country-specific samples. Furthermore, questionnaires to measure process evaluation were used to compute a total process evaluation score for teachers and parents/caregivers. No significant intervention effects on preschoolers’ snack intake were found (all p > 0.003). In general, no different effects of the intervention on snack intake were found according to kindergarten teachers’ and parents’/caregivers’ process evaluation scores. The lack of effects could be due to limited intervention duration and dose. To induce larger effects on preschoolers’ snack intake, a less standardized intervention which is more tailored to the local needs might be needed.